RELATIONSHIP QUALITY OF SERVICE AND SERVICESCAPE WITH CUSTOMER SATISFACTION IN THE MAIN BRANCH OFFICE OF HEALTH IN BOGOR - Hari Muharam; Sufrin Hannan; Yerry Gerson Rumawak (UNIVERSITAS PAKUAN, 2020)
The purpose of this study is to determine whether there is a relationship between service quality and servicescape with customer satisfaction both partially and together. The population in this study were customers of the Main Branch Office BPJS Health Bogor City as many as 457 customers, the sampling technique using the Slovin formula after 231 samples were obtained. The research instrument was a questionnaire. The collected data is then processed using simple and multiple correlation analysis techniques with the help of SPSS (Statistical Package for Social Science) software version 25.0. The results showed that: 1. Service quality is partially correlated positively to strong criteria with customer satisfaction, 2. Servicescape is partially strongly positively related to customer satisfaction, 3. Service quality and Servicescape together are positively highly correlated with customer satisfaction with correlation coefficient values equal to 0.830 then the functional relationship obtained by the equation Ŷ = 16.043 + 0.550X1 + 0.589X2 and the coefficient of determination or contribution of service quality and servicescape together with customer satisfaction of 0.688 or 68.6%.